2022
DOI: 10.1093/nop/npac003
|View full text |Cite
|
Sign up to set email alerts
|

A randomized feasibility study evaluating temozolomide circadian medicine in patients with glioma

Abstract: Background Gliomas are the most common primary brain tumor in adults. Current treatments involve surgery, radiation, and temozolomide (TMZ) chemotherapy, however prognosis remains poor and new approaches are required. Circadian medicine aims to maximize treatment efficacy and/or minimize toxicity by timed delivery of medications in accordance with the daily rhythms of the patient. We published a retrospective study showing greater anti-tumor efficacy for morning, relative to evening, administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…Damato AR et al reported no significant difference in adverse events, quality of life, or OS in prospective randomized TMZ chronotherapy trials. 123 For high‐grade glioma patients, radiotherapy treatment time of the day (RT‐TTD) did not influence progression‐free survival and OS between patients treated in the morning or afternoon. 129 The heterogeneity of each study is worth our attention.…”
Section: Future Perspectivementioning
confidence: 96%
See 4 more Smart Citations
“…Damato AR et al reported no significant difference in adverse events, quality of life, or OS in prospective randomized TMZ chronotherapy trials. 123 For high‐grade glioma patients, radiotherapy treatment time of the day (RT‐TTD) did not influence progression‐free survival and OS between patients treated in the morning or afternoon. 129 The heterogeneity of each study is worth our attention.…”
Section: Future Perspectivementioning
confidence: 96%
“…However, the results of chronotherapy for temozolomide and radiation therapy in glioma are currently controversial. Damato AR et al reported no significant difference in adverse events, quality of life, or OS in prospective randomized TMZ chronotherapy trials 123 . For high‐grade glioma patients, radiotherapy treatment time of the day (RT‐TTD) did not influence progression‐free survival and OS between patients treated in the morning or afternoon 129 .…”
Section: Future Perspectivementioning
confidence: 98%
See 3 more Smart Citations